Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Pada PT. Outletz Worldwide Indonesia - Wulansari, Retno (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Understanding the factors that influence consumer purchasing behavior is essential for companies operating in competitive markets, such as PT. Outletz Worldwide Indonesia. As consumers become more selective, businesses must identify what drives their buying decisions. This research was conducted to explore how price and product quality, both individually and together, affect purchasing decisions. A quantitative method with descriptive and associative approaches was used, supported by data collected through questionnaires. Various statistical analyses were applied to ensure the reliability and validity of the findings. The study found that both price and product quality have a significant and positive impact on consumer purchasing decisions. Price influences customers by affecting their perception of value and affordability, while product quality shapes their trust and satisfaction with the brand. When combined, these two factors strengthen their influence on buying behavior. The results imply that PT. Outletz Worldwide Indonesia should focus on maintaining competitive pricing strategies while also ensuring consistent product quality. Doing so can lead to stronger customer loyalty, increased purchase intention, and better overall market performance. These findings provide actionable insights for business development and customer relationship strategies.